Effect of Physical Activity on the Prevalence of Metabolic Syndrome and Left Ventricular Hypertrophy in Apparently Healthy Adults - Dao-Fu Dai; Juey-Jen Hwang; Chi-Ling Chen; Fu-Tien Chiang; Jiunn-Lee Lin; Kwan-Lih Hsu; Chuen-Den Tseng; Yung-Zu Tseng (Journal of the Formosan Medical Association, 2010)
Metabolic syndrome and left ventricular hypertrophy (LVH) carry high cardiovascular risks. We performed a cross-sectional study to evaluate the effect of different amounts of physical activity (PA) on the prevalence of metabolic syndrome and LVH in our study population. Methods: This study was a cross-sectional survey of 1494 apparently healthy subjects: 776 men with a mean age of 57.6 + 12.3 years, and 718 women with a mean age of 56.4+ 11.0 years. The metabolic syndrome was defined according to modified criteria of the National Cholesterol Education Program Adult Treatment Panel III. LVH was diagnosed by electrocardiography voltage criteria. The amount of PA was determined with a questionnaire and stratified into low, moderate or high levels. Results: The prevalence of metabolic syndrome and its components was as follows: metabolic syndrome, 15.5%; obesity, 29.7%; high triglyceride level, 21.7%; low high-density lipoprotein-cholesterol level, 35.9%; high blood pressure, 56.9%; and impaired fasting glucose, 13.1%. A high amount of PA (> 14km per week walking distance) was significantly associated with lower prevalence of metabolic syndrome [odds ratio (OR) = 0.53, p = 0.001], lower prevalence of obesity (OR = 0.56, p = 0.001), triglyceridemia (OR = 0.58, p = 0.007) and LVH (OR=0.37, p = 0.006). Conclusion: This study suggests that high amounts of PA are inversely correlated with the prevalence of metabolic syndrome and LVH in men and women.